A Time Series Analysis of The Production Performance of Principal Crops in Three Agro-Climatic Zones of Rajasthan - Mehta, Arun C; Joshi, B R; Kalla, Jagdeesh C (Annals of Arid Zone, 2016)
The production performance of principal. crops are composed of systematic and random fluctuations over time. An attempt has been made in this study to isolate systematic from random fluctuations of the production performance of principal crops in three distinct agroclimatic regions of the state of Rajasthan and the study has revealed very few crops in any region with a persistently significant trend. The decomposition of the trend for exploring the cyclical trends revealed a rather week presence of cycles for bajra, jowar and sesamum only. The study conclusively proved that over time, production performance of principal crops have mainly been a result of stationary random progresses. It thus seems inevitable to conclude that except wheat, the existing technology has hot been able to shift the production functions of these crops significantly, in the state of Rajaslhan.